2019
DOI: 10.1007/s12528-019-09241-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting student dropout in MOOCs: a cause and effect decision‐making model

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 66 publications
(92 reference statements)
4
72
1
7
Order By: Relevance
“…Figure 2 shows the percentage of total students by age distribution. Most of the participants were adults, similar to in other studies [10,22,23]. The majority age group was from 25 to 35 years old in the three editions (37.5%, 29.9%, and 38.7%, respectively), which reflects the goal attainment for the previously defined targeted audience in the course design, without prejudice to the original open and massive nature of an MOOC.…”
Section: Sociodemographic Characteristics Of Respondent Participantssupporting
confidence: 80%
See 2 more Smart Citations
“…Figure 2 shows the percentage of total students by age distribution. Most of the participants were adults, similar to in other studies [10,22,23]. The majority age group was from 25 to 35 years old in the three editions (37.5%, 29.9%, and 38.7%, respectively), which reflects the goal attainment for the previously defined targeted audience in the course design, without prejudice to the original open and massive nature of an MOOC.…”
Section: Sociodemographic Characteristics Of Respondent Participantssupporting
confidence: 80%
“…As shown in Table 2, the second edition was the most popular, with 2331 students enrolled, where 39.36% started the MOOC, and 36.80% of the students who had started the course finished it. These rates are higher than those of several indicated studies [9,10] in which the completion rates varied between 2% and 23%. The third edition had fewer students enrolled due to the circumstances from the COVID-19 pandemic, and this edition had scarce resources, especially in terms of dissemination on social networks.…”
Section: Sociodemographic Characteristics Of Respondent Participantscontrasting
confidence: 66%
See 1 more Smart Citation
“…A lack of social interaction is one of the reasons that online learners feel lonely, which has a negative impact on online learning (Moreno-Marcos et al 2019). If online learners persist in participating in the course discussion forum, the functions of support and companionship in the course discussion forum will be enhanced (Aldowah et al 2019). Social learning and peer learning are important factors in promoting online learner participation (Swinnerton et al 2017).…”
Section: Social Interaction In Mooc Discussion Forumsmentioning
confidence: 99%
“…Although MOOCs are currently seen as the perfect alternative to quality education, past studies showed that MOOCs are flawed with low completion and high dropout rates (Yang et al, 2013;Khalil and Ebner, 2014;Hussain et al, 2016;Liyanagunawardena et al, 2014;Veletsianos and Shepherdson, 2016). Student dropout in MOOCs is a keyinterest to be concerned about in the higher learning institutions and among policy makers which was mainly triggered by issuesbeyond the control of the institutions (Aldowah et al, 2019).Out of the 90% dropout rates, among the reasons given were due to having no one to turn to and feeling of isolation (Hew and Cheung, 2014;Khalil and Ebner, 2014).…”
Section: Introductionmentioning
confidence: 99%